2017
DOI: 10.1103/physrevphyseducres.13.010132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of representational competence in kinematics

Abstract: A two-tier instrument for representational competence in the field of kinematics (KiRC) is presented, designed for a standard (1st year) calculus-based introductory mechanics course. It comprises 11 multiple choice (MC) and 7 multiple true-false (MTF) questions involving multiple representational formats, such as graphs, pictures, and formal (mathematical) expressions (1st tier). Furthermore, students express their answer confidence for selected items, providing additional information (2nd tier). Measurement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 45 publications
3
36
0
2
Order By: Relevance
“…However, little is known about the influence of the subject context (e.g., finance or physics) on students' confidence ratings and about the ability to judge one's own performance in the context of graphs. Since confidence ratings are found to be an efficient tool to indicate the existence of misconceptions and learning difficulties [14], the assessment of students' response confidence rating in this study enriches the research about students' misconceptions [8].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, little is known about the influence of the subject context (e.g., finance or physics) on students' confidence ratings and about the ability to judge one's own performance in the context of graphs. Since confidence ratings are found to be an efficient tool to indicate the existence of misconceptions and learning difficulties [14], the assessment of students' response confidence rating in this study enriches the research about students' misconceptions [8].…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, it was found that poorly performing students grossly overestimated their performance, which is widely known as the Dunning-Kruger effect [13]. This effect was recently validated in PER [9] and could also be observed in problems testing the representational competence of physics students in the context of kinematics [14]. However, little is known about the influence of the subject context (e.g., finance or physics) on students' confidence ratings and about the ability to judge one's own performance in the context of graphs.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Representational fluency (i.e., the ability to dynamically pass from one representational format of a concept to another) is very important in physics and it is considered a sign of expertise [72,73]. Specific instruments for assessing students' representational fluency have been designed, such as the KiRC inventory for kinematics [74], and, on a more interdisciplinary perspective, the representational fluency survey [75].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, the TUG-K has been used as a preand posttest to investigate the effectiveness of instructions (e.g., video-based motion analysis [5]) or to study the relationship between the understanding of kinematics graphs and other variables (e.g., gender) [6]. The test has also been used as a reference to design new, related tests: for example, a test to assess the understanding of graphs in the context of calculus [2], the kinematics concept test [7] or the kinematics representational competence inventory [8]. For the TUG-K, the graphs of all test items relate to motion in one dimension and the items address the concepts of graph slope and area under the curve for different objectives [1].…”
Section: Introductionmentioning
confidence: 99%